Harismele părintelui duhovnicesc în epistolele Sfântului Simeon Noul Teolog - Maxim, Sergiu-Dan (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
We can not speak of a high spiritual life without a spiritual father. Has been written about this in the life of the Christian in both the patristic and the neopatristic eras. The importance of the spiritual father is also addressed by Saint Simeon the New Theologian, especially in his epistles. In these epistles, Saint Simeon raises a very important issue, that of the necessity of the ordination of the spiritual father. I will address this issue from the perspective of the Saint’s time as well as from the perspective of today. In addition to those mentioned, Simeon also speaks of the necessity of the confessor. Finally, he paints a portrait of the confessor by emphasizing three requirements that he is obliged to observe: intercessor, healer and counselor.